The Effect of Parent Distraction Coaching Used The Toy on Pain Intensity of 1-5 Year-Old Children During Iv (Intravenous) Insertion - Afrida Ristia; Djatnika Setiabudi; Ai Mardiyah (Faculty of Nursing Universitas Padjadjaran, 2018)
intravenous insertion is the cause of pain that the children most commonly experience when children are being hospitalised. Repeated and insurmountable in early childhood, it will impact trauma to the child, so that pain management is a main priority for nurses. However, nurses have barrier to implement pain management effectively. Therefore, involvement of the parents in pain management was so important. One of the non-pharmacological pain management involving parents is distraction by the parent (Parent Distraction Coaching). The purpose of this research was to examined the difference intensity of pain children from ages 1-5 years old between intervention group and control group during intravenous insertion. This research uses quasi experimental methode by applying the pre-experimental design which is called the intact group comparison. Through the consecutive sampling, the data has been collected from 17 children in each group, both control and intervention groups. Respondents in the intervention group were the children undergoing the intravenous insertion and they were accompanied by their parents' distraction after the parents got the parental distraction coaching, while respondents in the control group were the children undergoing the intravenous insertion in accordance with the hospital procedures but they were not accompanied by their parents' distraction. The assessment of pain intensity was done by using FLACC instruments (Face, Legs, Activity, Cry, and Consolability). The data were analyzed descriptively and tested by using inferential t test-independent where the value of p < 0.05. From the results of the statistical tests using t test-independent test, the value of p obtained is 0.005 (p value <0.05). This value indicates that there is a significant difference between the intensity of pain experienced by children in the control group and in the intervention group during the intravenous insertion. Based on these results, nurses are expected to be aware of the importance of parents or family involvement in reducing the pain experienced by children during intravenous insertion, so that the implementation of pain management in children becomes more effective.